THE LITERARY DEVELOPMENT OF THE S TRADITION – A NEW PARADIGM - Hempel, Charlotte 1966- (2006)
This article takes another look at the much debated question of the literary development of the S tradition. Rather than focusing on variants between the different manuscripts, which have been the focus of earlier studies, it is argued that elements of continuity between manuscripts and discontinuity within individual manuscripts, especially also within 4QS, shed further light on this question. It is proposed that the earliest forms of the tradition are to be found in the shared material.